The Implementation of the Singing Method in Enhancing Students’ Memorization of Arabic Vocabulary - Rika Ariani; Muhamad Hasyim; Nurpiana; M. Rizal Mufradi; Luqiana Khaironi; Rauhatul Hikmah; Muh. Rofi’i Sholbi; Nanda Kurnia; Lalu Daud Azizurrahman (Journal of Scientific Studies and Multidisciplinary Research, 2026)
This study investigates the implementation of the singing method in enhancing students’ memorization of Arabic vocabulary and examines its level of effectiveness based on findings from previous empirical research. Vocabulary mastery remains a fundamental challenge in Arabic language learning due to limited exposure, monotonous instructional strategies, and low student motivation. Therefore, innovative instructional approaches that integrate cognitive and affective learning dimensions are needed. This research employed a qualitative literature review design by systematically analyzing scholarly publications published between 2016 and 2025 related to music-based language learning, singing methods, and vocabulary acquisition. Data were collected through database searches, screening procedures, and thematic analysis to identify patterns, instructional models, and effectiveness indicators reported in previous studies. The findings indicate that the singing method provides significant pedagogical benefits in vocabulary memorization through the integration of melody, rhythm, and repetition, which function as mnemonic devices that facilitate memory encoding and retention. Structured implementation models consisting of pre-activity preparation, guided singing practice, and reinforcement activities were identified as effective instructional procedures. The literature also demonstrates that singing-based learning improves pronunciation accuracy, student motivation, engagement, and classroom participation while reducing learning anxiety. Empirical evidence consistently shows that students exposed to singing-based instruction achieve better vocabulary recall and longer retention compared to conventional teaching methods. However, effectiveness is influenced by factors such as repetition frequency, teacher competence, learner characteristics, and instructional design quality. In conclusion, the singing method represents an effective and engaging pedagogical strategy for enhancing Arabic vocabulary memorization and supporting meaningful language learning experiences.